Priority setting in health in the Sri Lankan context: process and mechanisms - Nihal Abeyesundere (College of Community Physicians of Sri Lanka, 2001)
The important role played by public health has only been realised in the last three decades. The Alma-Ata Conference in 1978 revolutionised the role that public health played. The concept of equity and the availability of 'health care for the poor and disadvantaged were emphasised. Health promotion and priority health setting were also defined Priority health setting helps to rationalise health service delivery with scarce financial resources. Sri Lanka has, since independence, provided free education and free health to its people. However, with rising costs the country has realised that priority setting in health is essential. Lanka is in the transition period. It has a double burden of disease both communicable and non-communicable. Although malaria, dengue haemorthagic fever, Japanese encephalitis, diarrhoeas and acute respiratory infections still affect the community, emerging diseases such as ischaemicheart diseases, cerebro-vascular accidents, diabetes and cancer play a major role in morbidity patterns. Sri Lanka has also one of the highest suicide rates in the world. Pesticide poisoning of adolescents and young adults take a heavy toll. Changing socio-economic conditions and an increase in life expectancy have made the care for the elderly a problem, It is also affected by the conflict situation in the North East and smoking related diseases.   The country has achieved spectacular successes, which are indicated by the low vital health statistical parameters. It has provided its people with medical institutions within a five mile radius. Life expectancy especially for females has been substantially increased. Sri Lanka has eradicated smallpox, achieved universal child immunization and should eradicate polio in the near future. Some of the failures have been the resurgence of malaria since 1967 due to logistical and administrative constraints.   Local Government and community apathy to hygiene, clean water and sanitation have led to epidemics of DHF and diarrhoeal diseases. There is inadequate access to reliable health information.   The open market economy has had an adverse effect on health care delivery. Steps taken to cushion the effects of the WTO and TRIPS arrangements and provide Sri Lanka with drugs at affordable prices have also been recommended. The sectoral approach to health related problems has been emphasized focusing on inter-sectoral linkages, partnerships and community-based actions. Priority health areas such as the problems of HIV/AIDS, mental health, the Tobacco free initiative and care for the elderly have been addressed. What the health services are presently doing to overcome these problems and future strategies to address them have been indicated.   Maximisation of resources available for health has also been described, Health expenditure is only 1.6% of the GDP. Of this, only 16% is allocated for preventive health, Sri Lanka must also maximise its resources through partnerships and more effective use of donor resources. The problems of lack of skilled managers, development of the second line of, management, the mal-distribution of medical officers and the shortage of nurses, paramedical and public health personnel is also being addressed. The use of trained volunteers especially in conflict areas has been advocated. Regional cooperation on health priorities is carried out through the South-East Asia Regional Office of WHO and the South-Asia Association of Regional Cooperation.